Strategic Analysis for Sustainable Tourism Development: A SWOT-Based Approach to Ekasoghi Beach Tourism in Sumenep District - Safitri, Laela; Kurriwati, Nirma; Yulistiyono, Herry (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Ekasoghi Beach Tourism is one of the marine tourism destinations in Sumenep Regency. This tour has natural beauty. with tourist attractions in Sumenep and has natural wealth that the tourism sector should be proud of which not only provides tourist resources but also contributes to the environment and society in its development. Sumenep Regency is a city that has a variety of tourist attractions, one of which is Ekasoghi Beach, and this beach has a very beautiful and sparkling view at night. Tourism potential in Indonesia can be a force that must be taken into account under certain conditions. Natural beauty is the main attraction. And apart from the rich culture and art of its people, Ekasoghi Beach is one of the beaches that is of interest to many local people. The purpose of this research is to determine the strengths, weaknesses, opportunities and threats of the Ekasoghi Beach tourist attraction, and to find the right strategy for developing this tourism. The method used is descriptive qualitative method, in this research the data analysis used is SWOT analysis. The results obtained in this research state that Ekasoghi Beach has implemented internal and external factors that influence the development of tourism development strategies.